Impact of Spontaneous Fermentation on the Physicochemical and Sensory Qualities of Cacao - Lucas Fernando Quintana-Fuentes; Alberto García-Jerez; Ana Carolina Rodríguez-Negrette; Nurys Tatiana Hoyos-Merlano; Armando Alvis-Bermúdez (Fermentation)
Fermentation is a fundamental technique that allows us to obtain high-quality cacao beans and derived products. Therefore, it is necessary to apply fermentation correctly to maximize product quality. Fermentation techniques vary by region and include piles, trays, wooden boxes, baskets, and platforms. During these processes, several factors influence the physicochemical and sensory characteristics of cacao beans. The factors that influence these characteristics are the frequency of turning, the genotype of the bean, and the duration of fermentation. This review aims to explore how the fermentation method, turning frequency, bean genotype, and fermentation duration affect the physicochemical and sensory qualities of cacao beans. To this end, an exhaustive search for recent information on the most commonly used fermentation methods in cacao-producing countries over the last 10 years was carried out. The fermentation method in wooden boxes or crates is the most commonly used method worldwide. The most common turning frequency is 24 or 48 h, which is considered the most suitable time for obtaining cacao beans with better sensory attributes, such as floral and fruity aromas, and a lower level of acidity. Finally, a relationship was found between the genotype and the optimal fermentation time of cacao: about 4 days for Criollo cacao, approximately 5 days for Forastero cacao and between 1.5 and 10 days for Trinitario cacao.